Faecal calprotectin effectively excludes inflammatory bowel disease in 789 symptomatic young adults with/without alarm symptoms: a prospective UK primary care cohort study. Issue 8 (5th March 2018) - Walker, G. J.; Moore, L.; Heerasing, N.; Hendy, P.; Perry, M. H.; McDonald, T. J.; Debenham, T.; Bethune, R.; Bewshea, C.; Hyde, C.; Heap, G. A.; Singh, A.; et al.
Summary: Background: Primary care faecal calprotectin testing distinguishes inflammatory bowel disease (IBD) from functional gut disorder in young patients presenting with abdominal symptoms; however, previous evaluations have excluded patients with alarm symptoms. Aims: We sought to evaluate the diagnostic accuracy of calprotectin to distinguish IBD from functional gut disorder in young adults in whom general practitioners (GPs) suspected IBD; including patients reporting gastrointestinal alarm symptoms. We hypothesised that calprotectin would reduce secondary care referrals and healthcare costs. Methods: We undertook a prospective cohort study of 789 young adults (18‐46 years old) presenting with gastrointestinal symptoms to 49 local general practices that had undergone calprotectin testing (1053 tests: between Jan 2014 and May 2016) because of suspected IBD. We considered calprotectin levels of ≥100 μg/g positive. Primary and secondary care records over 12 months from the point of calprotectin testing were used as the reference standard. Results: Overall, 39% (308/789) patients reported gastrointestinal alarm symptoms and 6% (50/789) tested patients were diagnosed with IBD. The positive and negative predictive values of calprotectin testing for distinguishing IBD from functional gut disorder in patients with gastrointestinal alarm symptoms were 50% (95% CI 36%‐64%) and 98% (96%‐100%): and in patients without gastrointestinal alarm symptoms were 27% (16%‐41%) and 99% (98%‐100%), respectively. We estimate savings of 279 referrals and £160 per patient. Conclusions: Calprotectin testing of young adults with suspected IBD in primary care accurately distinguishes IBD from functional gut disorder, even in patients with gastrointestinal alarm symptoms and reduces secondary care referrals and diagnostic healthcare costs.